Parenting needs of selected urban and rural families bases for guidance program for parents - Sarillana, Ma. Zita Annette Sanchez; Ho, Leticia P.; Ronquillo, Carolyn U.; De Guzman, Ligaya S. (2007)
The research was an attempt to study the needs and concerns of parents of both urban and rural communities. It was a qualitative/descriptive research. The key tools were in depth interviewing and focus group discussion. Most of the participants were housewives. It was done among the families from Veterans Village, Project 7, Quezon City, Manila and Estrella, Rizal, Nueva Ecija. The researcher highly recommends a parenting program for the urban and rural parents of today which will prioritize on care giving parenting needs, on protecting parenting needs, on nurturing, etc. They need to develop interest outside family, support network for stay at home moms, agencies that can help parents, conflict resolution skills, improved socialization skills support system to encourage parents, parent education programs, financial planning, teach parents creativity,and how to spend time with kids.
"May 2007."
Thesis (M. A. Education : Guidance)--University of the Philippines Diliman.
Keywords: Parenting -- Philippines; Preschool children -- Philippines; Parent and child -- Philippines